1992
DOI: 10.5254/1.3538604
|View full text |Cite
|
Sign up to set email alerts
|

A New Process for the Preparation of Highly Saturated Nitrile Rubber in Latex Form

Abstract: A novel process for the preparation of highly saturated nitrile rubber latex has been developed. This process directly converts NBR latex into HNBR latex in one reaction step. The key to the process is the efficient in-situ generation of diimide within the latex by the oxidation of hydrazine hydrate in the presence of a catalyst. At 40–70°C, diimide smoothly and selectively reduces the olefinic bonds while leaving other functionalities unaffected. The process operates at ambient pressures and produces nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…This has been proven in Parker and Roberts' work 9 by complexing copper ions in water with aqueous ethylenediamine tetraacetic acid tetraso-(1) dium salt (Na 4 EDTA). Their results showed that no double bonds could be reduced in this case.…”
Section: Location and Concentration Of Copper Ionmentioning
confidence: 99%
See 3 more Smart Citations
“…This has been proven in Parker and Roberts' work 9 by complexing copper ions in water with aqueous ethylenediamine tetraacetic acid tetraso-(1) dium salt (Na 4 EDTA). Their results showed that no double bonds could be reduced in this case.…”
Section: Location and Concentration Of Copper Ionmentioning
confidence: 99%
“…Another important function of a carboxylated surfactant is to form hydrozinium carboxthe SP and LP latex systems. It should be mentioned that the purpose of this experiment was to ylate 9 by which the hydrozinium ion could also be present on the particle surface.…”
Section: Location and Concentration Of Copper Ionmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of emulsion may have potentially important applications for the coating industry. [22][23][24] In the following, two proHydrogenation Process cesses for the direct hydrogenation of NBR emulsion have been investigated and the results are All the reactions were carried out in a stainless steel autoclave. The NBR copolymer emulsion was presented.…”
Section: -29mentioning
confidence: 99%